Reality of career performance for public school principals in south Hebron directorate from the viewpoint of teachers - Saleh, Muhammad Imran; Tokhman, Muhammad Radwan (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the reality of the performance of government school principals in the Education Directorate/ South Hebron from the viewpoint of teachers, in addition to showing the difference in views in the reality of the performance of the principals of these schools according to the gender variable, educational qualification, years of experience, and educational stage. In this study, the two researchers used the descriptive method relying on a questionnaire as a study tool. The study was conducted in the first semester of the academic year 2019/2020 and the study community will consist of all male and female teachers of government schools affiliated to the Palestinian Ministry of Education in the Directorate of Education/ South Hebron working in (172) schools. The results of the study showed: The reality of the performance of the directors of public schools in the Education Directorate/ South Hebron from the teachers' point of view came to a large extent, where the relative weight reached (71.1). There were no statistically significant differences at the level of significance ((0.05≥α) between the averages of responses of public school teachers in the South Hebron District with regard to assessing the performance of their directors due to gender and educational levels. The presence of statistically significant differences at the level of significance ((0.05≥α) among the averages of responses of government school teachers in the South Hebron Directorate with regard to evaluating the performance of their directors attributable to the variables of the educational qualification, and experience. The differences came in favor of the educational qualification (master and above), and came in favor of experience from 5 to 10 years. Accordingly, the researchers recommended some recommendations, including: Focus on training school principals to develop communication with the local community, parents and local community institutions, increasing the interest of school administrators in the technical aspect in school administrations related to methods of educational supervision, measurement and evaluation, activating the role of the principal as a resident supervisor, and pay attention to internal relations within the educational institution by the principals of public schools.
Keywords: The reality of school principals’ performance; Southern Hebron Education Directorate; performance appraisal; principal description